Prostorski vplivi slovenske regionalne politike - Nared, Janez (Geografija Slovenije, 2007)
This study attempts to illustrate the role of regional policy in the development of spatial structures and simultaneously determine the success and the possibly diverse response of individual instruments of regional policy to the structures of problem areas. We established that the influences of the regional policy are relatively minor, a consequence of the scant financial means devoted to the stimulation of regional development, the lack of power of the overall regional policy relative to all development currents introduced by inclusion in the European Union, and very aggressive globalization. However, we are able to cite some of its successes, mostly visible on the local level, although at higher levels their influence weakened. Because the goals of the regional policy in the previous period have not been achieved, we suggest some changes that would either strengthen the current method of stimulating regional development or abandon it altogether and turn toward the active stimulation of the polycentric network of cities that would result in the greater competitiveness of individual centers, which we hope would also have positive effects in their immediate hinterland.